Innovative Vaccine Technologies: Current Landscape and Future Prospects in Preventive Medicine - Satish Kumar Sarankar; Santosh Ojha; Brajesh Rajak; Sushma Somkuwar (International Journal of Vaccines, 2024)
This review article presents a comprehensive analysis of recent advancements and emerging trends in vaccine development, offering insights into the dynamic landscape of preventive medicine. Delving into a spectrum of infectious diseases, including influenza, HIV/AIDS, malaria, tuberculosis, respiratory syncytial virus (RSV), Group B Streptococcus (GBS), norovirus, and chikungunya, the review highlights innovative approaches and breakthroughs in vaccine technology. It explores efforts to develop universal influenza vaccines, long-awaited HIV vaccines, and next-generation malaria and tuberculosis vaccines. Additionally, the review examines ongoing clinical trials for RSV, GBS, norovirus, and chikungunya vaccines, emphasizing the importance of targeting vulnerable populations and addressing global health challenges. Furthermore, the review discusses the implications of precision vaccinology, immunoengineering, and equitable vaccine distribution in shaping the future of public health. By synthesizing diverse perspectives and recent research findings, this article contributes to the discourse on vaccine innovation and underscores the critical role of vaccines in disease prevention and global health security.
Keywords: Immunoengineering; Infectious Disease; Vaccine; Viral Vectors; mRNA